Determination of Serum Adiponectin Levels in Normal Weight Women with Polycystic Ovary Syndrome - Hamdi, Rana A.; Mohammed, Nawar S.; AL-Naddawi, Afraa M. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age with primary manifestations of infertility, menstrual dysfunction and clinical or biochemical hyperandrogenism (hirsutism, acne and elevated androgen). Adiponectin is the most abundant adipokine. It has insulin-sensitizing, anti-atherogenic, and antiinflammatory actions. Objective: Low adiponectin levels in women with PCOS have been largely attributed to obesity which is common among these patients. Therefore, the aim of this study was to measure adiponectin levels in normal weight women with PCOS and its contribution to development of disease. Subjects and Methods: Fifty two (52) women were included in this study with age range (21-34 years). Subjects were divided into two groups: group A: twenty seven (27) women with PCOS and group B: twenty five (25) women without PCOS (serve as controls). PCOS can be diagnosed when two of the three following criteria are present (oligoovulation and/or anovulation, clinical and/or biochemical hyperandrogenism and polycystic ovaries as defined by ultrasonography). Results: Mean serum adiponectin level was significantly lower in women with PCOS comparing to those BMI-matched controls (P=0.000). Conclusion:Serum adiponectin levels are not independently determined by the degree of obesity in women but underlying disease may also have some role and this may due to insulin resistance in these patients thus determining serum adiponectin may serve as a useful marker in detecting cases of normal weight women with PCOS.